Helicobacter pylori Induces Cell Migration and Invasion Through Casein Kinase 2 in Gastric Epithelial Cells. Issue 6 (23rd July 2014) - Lee, Yeo Song; Lee, Do Yeon; Yu, Da Yeon; Kim, Shin; Lee, Yong Chan
Abstract : Background: Chronic infection with Helicobacter pylori ( H. pylori ) is causally linked with gastric carcinogenesis. Virulent H. pylori strains deliver bacterial CagA into gastric epithelial cells. Induction of high motility and an elongated phenotype is considered to be CagA‐dependent process. Casein kinase 2 plays a critical role in carcinogenesis through signaling pathways related to the epithelial mesenchymal transition. This study was aimed to investigate the effect of H. pylori infection on the casein kinase 2‐mediated migration and invasion in gastric epithelial cells. Materials and Methods: AGS or MKN28 cells as human gastric epithelial cells and H. pylori strains Hp60190 (ATCC 49503, CagA + ) and Hp8822 (CagA − ) were used. Cells were infected with H. pylori at multiplicity of infection of 100 : 1 for various times. We measured in vitro kinase assay to examine casein kinase 2 activity and performed immunofluorescent staining to observe E‐cadherin complex. We also examined β‐catenin transactivation through promoter assay and MMP7 expression by real‐time PCR and ELISA. Results: H. pylori upregulates casein kinase 2 activity and inhibition of casein kinase 2 in H. pylori‐ infected cells profoundly suppressed cell invasiveness and motility. We confirmed that casein kinase 2 mediates membranous α‐catenin depletion through dissociation of the α‐/β‐catenin complex in H. pylori‐ infected cells. We also found that H. pylori induces β‐catenin nuclear translocation and increases MMP7 expressions mediated through casein kinase 2. Conclusions: We show for the first time that CagA + H. pylori upregulates cellular invasiveness and motility through casein kinase 2. The demonstration of a mechanistic interplay between H. pylori and casein kinase 2 provides important insights into the role of CagA + H. pylori in the gastric cancer invasion and metastasis.